Liver Cancer Gene Discovery Using Gene Targeting, Sleeping Beauty, and CRISPR/Cas9 - Kieckhaefer, Julia E.; Maina, Flavio; Wells, Rebecca G.; Wangensteen, Kirk J. (Seminars in Liver Disease, 2019)
Hepatocellular carcinoma (HCC) is a devastating and prevalent cancer with limited treatment options. Technological advances have enabled genetic screens to be employed in HCC model systems to characterize genes regulating tumor initiation and growth. Relative to traditional methods for studying cancer biology, such as candidate gene approaches or expression analysis, genetic screens have several advantages: they are unbiased, with no a priori selection; can directly annotate gene function; and can uncover gene–gene interactions. In HCC, three main types of screens have been conducted and are reviewed here: (1) transposon-based mutagenesis screens, (2) knockdown screens using RNA interference (RNAi) or the CRISPR/Cas9 system, and (3) overexpression screens using CRISPR activation (CRISPRa) or cDNAs. These methods will be valuable in future genetic screens to delineate the mechanisms underlying drug resistance and to identify new treatments for HCC.
Keywords: hepatocellular carcinoma; genetic screening; Sleeping Beauty transposon; CRISPR; hydrodynamic injection